2021
DOI: 10.1016/j.jgo.2021.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for systemic therapy in older patients with metastatic melanoma: Results from the Dutch Melanoma Treatment Registry

Abstract: Background: The incidence of metastatic melanoma is increasing in all ages. Multiple trials with targeted drugs and immune checkpoint inhibitors showed improved survival in metastatic melanoma. However, patients aged ≥75 years are often under-represented in clinical trials, therefore raising questions on safety and efficacy of treatment. Patients and methods: We analyzed a real-world cohort of 3054 patients with metastatic melanoma stratified for age (≤65 years, 66-74 years and ≥ 75 years), and BRAF status, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(75 reference statements)
1
1
0
Order By: Relevance
“…We argue that the effect of age is strong, even after correcting for risk factors. This has been shown in a previous study by Jochems et al [22], where the difference in unadjusted and adjusted hazard ratio of age for death was small. Possibly, this is caused by the mix of risk factors: in our study, older patients have significantly worse ECOG PS but significantly less brain metastases and lower disease stage and less organ sites with metastases (Supplement 4).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We argue that the effect of age is strong, even after correcting for risk factors. This has been shown in a previous study by Jochems et al [22], where the difference in unadjusted and adjusted hazard ratio of age for death was small. Possibly, this is caused by the mix of risk factors: in our study, older patients have significantly worse ECOG PS but significantly less brain metastases and lower disease stage and less organ sites with metastases (Supplement 4).…”
Section: Discussionsupporting
confidence: 64%
“…Other explanations might be that patients have lived healthier after diagnosis with advanced melanoma, with better outcomes than the general population as a result. Previous studies of Jochems et al [22] and de Glas et al [23] studied outcomes of systemic therapy in older patients with metastatic melanoma. The study of Jochems et al used a registered variable for cause of death, and found borderline significance in 3-year melanomaspecific mortality between patients aged 60 years and !75 years.…”
Section: Discussionmentioning
confidence: 99%